The extent of the use of blended learning in public schools in Mafraq Governorate from the point of view of history teachers - Al-Alimat, Fawzia Muhammad AlMuslim (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to reveal the extent of the use of blended learning in public schools in Mafraq Governorate from the point of view of history teachers. The study for them consisted of a questionnaire consisting of (21) items. The study found the extent of the use of blended learning in public schools in Mafraq Governorate from the point of view of history teachers, which amounted to (4.06), which is a large degree according to the scale prepared for the study, and the results also showed that there are no statistically significant differences between the average responses of the study sample members towards The extent of the use of blended learning in public schools in Mafraq Governorate is attributed to the variables (gender, educational qualification, years of experience), where the value of the indicative level was greater than (0.05), and based on the results of the study, the researcher reached a set of recommendations, the most important of which was that History teachers should continue to write students’ homework so that they search for their answers by searching on the Internet, and the necessity of providing in the school an electronic specialist to help teachers employ blended learning in their classrooms constantly.
Keywords: Blended learning; public schools; Mafraq Governorate; history teachers